Future Self-Continuity Increases Responsibility during Covid-19 Restrictions : Kontinuitet s budućim ja povećava odgovornost tijekom ograničenja povezanih s bolešću COVID-19 - Simić, Andrej (Array, 2021)
The failure to engage in responsible behaviour is related to the inability to consider future consequences of actions. An experiment was conducted to examine whetherincreasing the vividness of the future self affects adherence and endorsement of COVID-19 safety measures. A total of 184 participants were randomly assigned to 3 groups. Depending on the experimental condition, they were tasked with writing a letter to other people (their friend), a proximal future self, and a distant future self. Participants in the distant future self and the other people conditions showed greater adherence intentions than proximal future self participants. No differences were found between the distant future self and the other people group. Further group differences were found in the endorsement of safety measures, with the distant-future self-group showing more condemnation than the other two groups. Commitment to the COVID-19 safety measures mediated the group differences on both dependent variables. The results are discussed within the framework of the Construal Level Theory and the Future Self-continuity model.